O poder simbólico das radiolas de reggae na cultura maranhense - Moreira Neto, Euclides Barbosa (2013)
Some four decades, gender reggae arrived in Maranhão land, coming from Jamaica and gaining significant peripheral portion of the population of St. Louis and the main urban centers of northern Maranhao. Without official support, this new genre gained the sympathy of the poor black youth from the edges of cities, wage, and with high rates of illiteracy, reframed and reinterpreted elements of local culture, acquiring characteristics. Among the most striking points deployed in the State of Maranhão with the culture of reggae, register with the technical configuration of the "radiogram reggae" with their sumptuous walls that impress connoisseurs, scholars and ordinary people who enter this world of entertainment for leisure and / or fun. Therefore, this research aims to understand how was the transposition of the reggae genre of Jamaica (Caribbean country) to Maranhão and the various ways in which this musical style was absorbed by the local people over time, since it came to be accepted not only by population of banks, but also for middle upper class of urban centers, the mainstream media and by their own official policy, establishing new boundaries of performance, determining specific models in the form of disputes in Circuit Regueiro, verifying diverse and conflicting interests, which identity established limits, convergence, tastes and class distinction, especially in the mode of production, consumption and publicity, giving emphasis to the radiogram of reggae that gained quite peculiar characteristics in Maranhão, in addition to various forms of relationship-style music for the people inhabits the region.